"Ghost tablet" husks excreted in feces in large bupropion XL overdose. (1st February 2019) - Overberg, Adam; Purpura, Andrea; Nanagas, Kristine
Abstract: Background: Extended-release medications are widely prescribed across the spectrum of medical specialties; however, there is heterogeneity in how they are formulated. Commonly, they consist of an insoluble matrix or shell from which drug elutes, which may then be observed by patients when excreted in feces. We describe the case of a patient who ingested a large amount of extended-release bupropion tablets and subsequently passed a large number of these so-called "ghost tablets" in his stool. Case Details: A 19-year-old male presented in status epilepticus following intentional overdose of an unknown substance. He had prolonged QRS and QT intervals on ECG, hypotension requiring vasopressors, and tachycardia, and progressed to cardiac arrest and respiratory failure. On hospital day 4, he passed several large bowel movements containing apparent tablets. Serum bupropion and hydroxybupropion levels performed on serum taken at time of admission were 1800 ng/mL and 4200 ng/mL, respectively. Case Discussion: "Ghost tablets, " the insoluble remnant of some extended-release dosage forms, have been previously reported to appear in patients' stool in the course of therapeutic dosing. We present the case of a considerable quantity of these ghost tablets recovered from stool following a large bupropion XL overdose. Conclusion: Healthcare providers should be aware of the potential for this phenomenon to occur in poisoned patients. It should be documented as physical evidence of overdose in addition to clinical evidence.